CLUSTERING TECHNIQUE IN GENERATING THE STUDENTS’ IDEAS - Putri Dini Meutia; Suryani; Ema Dauyah; Cut Mawar Helmanda; Rahmayani (Getsempena English Education Journal, 2019)
This research was conducted to know the influence of clustering technique in generating the students’ ideas in prewriting. The purpose of this research was to find out does the clustering technique influence the second grade students in generating their ideas in prewriting of explanation text. The research used a pre-experimental design. The design used one group pre-test – post-test. The main instrument in this research is a test. The sample of this research was the second grade students of SMAN 1 Kuta Baro. From the result, it was found that the mean score of pre-test was 50 and the mean score of post-test was 74.06 and the t-score was 16.10 and t –table was 2.13. It meant that t-score was higher than t-table. From the result above, Ha was accepted and H0 was rejected. It can be concluded that clustering technique is a good technique in prewriting activity. It is very useful for students in generating ideas. It also helps them to enhance their ability and motivation. Therefore, the application of clustering technique has a great influence on the students' performance and attitude towards the learning process especially in generating ideas in writing.